Mobile apps as urban communication tools for climate change in Loja, Ecuador - Cuesta Palacios, Elsa Katerine (2023)
This research explores user’s predisposition levels regarding eight mobile apps linked to sustainability and climate change. These users, community leaders, city officials and technology experts from Loja (Ecuador), provided their point of view through semi-structured interviews; a behavioral intention methodology was implemented to assess the results. The study concludes that user’s inclination to use these apps is low and that the challenge of the local public administration is to create a citizens’ lab to discuss and share actions that mitigate climate change using technologies.